2017
DOI: 10.11158/saa.22.7.13
|View full text |Cite
|
Sign up to set email alerts
|

Functional response of two Neoseiulus species preying on Tetranychus urticae Koch 

Abstract: Neoseiulus californicus and N. cucumeris are both potential candidates for the biological control of key pests in China. Whereas N. californicus has mainly been used to control spider mites, N. cucumeris has been released for the control of thrips and spider mites. To understand the potential of the combined use of N. californicus and N. cucumeris to suppress outbreaks of Tetranychus urticae, the predatory performance of these Neoseiulus species against different stages of T. urticae, either separately or in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
3
5
0
4
Order By: Relevance
“…For N. cucumeris, the fecundity here observed is much lower than that reported by AlAzzazy et al (2018). The daily T. urticae egg consumption (14.52) is in accordance with values obtained by Li & Zhang (2016) and Zheng et al (2017) and higher than those reported by AlAzzazy et al (2018).…”
Section: N Californicus N Cucumerissupporting
confidence: 88%
“…For N. cucumeris, the fecundity here observed is much lower than that reported by AlAzzazy et al (2018). The daily T. urticae egg consumption (14.52) is in accordance with values obtained by Li & Zhang (2016) and Zheng et al (2017) and higher than those reported by AlAzzazy et al (2018).…”
Section: N Californicus N Cucumerissupporting
confidence: 88%
“…Many predators with the Type II functional response model have been successfully used as biological control agents (Hughes et al, 1992;Fernandez-Arhex & Corley, 2003;Xiao & Fadamiro, 2010). The Type II functional response is also common among phytoseiid species such as Neoseiulus cucumeris (Oudemans, 1930) (Zheng et al, 2017), Neoseiulus womersleyi (Schicha, 1975) (Ali et al, 2011), Galendromus occidentalis (Nesbitt, 1951 (Xiao & Fadamiro, 2010), Neoseiulus californicus (McGregor, 1954) (Castagnoli & Simoni, 1999;Gotoh et al, 2004;Kustutan & Cakmak, 2009;Xiao & Fadamiro, 2010), Euseius finlandicus (Oudemans, 1915) (Shirdel, 2003), Euseius hibisci (Chant, 1959) (Badii et al, 2004), Iphiseius degenerans (Berlese, 1889) (Fantinou et al, 2012), Typhlodromus bagdasarjani Wainstein & Arutunjan, 1967 (Farazmand et al, 2012) and Kampimodromus aberrans (Oudemans, 1930) (Kasap & Atlihan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Phytoseiid mites received much attention due to their important roles in controlling phytophagous mites and other small arthropods such as thrips, whitefly and psyllids (Hoogerbrugge et al 2011;Knapp et al 2013;McMurtry et al 2013;Xu & Zhang 2015;Azevedo et al 2016;Silva et al 2016;Fathipour et al 2017;Liu & Zhang 2017;Patel & Zhang 2017a,b;Shakarami & Bazgir 2017;Song et al 2017;Ullah & Lim 2017;Zheng et al 2017). More than 2700 species have been recorded worldwide (Chant & McMurtry 2007;Ma et al 2016;Demite et al 2017).…”
Section: Introductionmentioning
confidence: 99%